Subduction-related Jurassic andesites in the northern Great Caucasus - Hess, Jürgen C.; Aretz, J.; Gurbanov, A. G.; Emmermann, R.; Lippolt, Hans J. (Geologische Rundschau, 1995)
During the Jurassic the major tectonic units of the Great Caucasus (Bechasyn, Front Range, Main Range and Southern Slope zone) were affected by intensive magmatic activity. Magmatism within the Bechasyn zone, the northernmost unit, which represents the southern part of the Variscan-consolidated Skythian platform is considered here. With the beginning of the Early Jurassic this zone was reactivated by subsidence, accompanied by the deposition of epicontinental shallow water sediments. The Lower Jurassic portion of this sedimentary pile was intruded by numerous sills which display a clear temporal and spatial evolution. The older basic rocks are lower in the profile than the younger, more acidic rocks. A set of 75 samples, representing all exposed sills and their feeder-dikes, was analyzed for major and 21 trace elements. All samples appear more or less affected by alteration under lower greenschist facies conditions. However, these alterations essentially took place on local scales and did not affect the overall chemistry. According to their main element composition the rocks constitute a calc-alkaline series ranging from basaltic—andesitic to rhyolitic. Most of the samples are andesites. Chemically, these andesites closely resemble modern orogenic andesites occurring at convergent plate margins. Altogether, the field evidence and the chemical and mineralogical data obtained show the investigated rocks to be comagmatic and derived from basalt—andesitic initial melts by magmatic fractionation processes. Tholeiitic melts have to be considered as parental magmas, which according to the trace element characteristics of the basalt-andesitic rocks, were generated from an enriched peridotitic mantle source. 87Sr/86Sr isotope ratios and σ18O values confirm the mantle origin of this rock series. The observed compositional evolution can be explained as a result of olivine and clinopyroxene fractionation of the tholeitic melts followed by amphibole and plagioclase separation. 40Ar/39Ar measurements on biotite and plagioclase phenocrysts separated from these rocks vary between 190 and 180 Ma and thereby place the magmatic activity in the late Early Jurassic, in good agreement with the stratigraphic observations. Genetically, the calc-alkaline rocks are related to a subduction zone of the Andean type. Their chemical and isotopic compositions and their age setting corroborate the plate tectonic models for the evolution of the Caucasus orogenic belt during the Jurassic.
Gesehen am 16.01.2023